PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA CAFE WAREG BENGKULU. - Julian Aryandi; Onsardi Onsardi (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2020)
The title of this research is the Effect of Servie Quality and Location on Purchasing Decisions at Bengkulu Wareg Cafe. This research is based on the importance of Purchasing in a company. Purchasing decisions can be affected by several factors. The factors might be Service Quality and Location. This research aims to analyze the effect of Service Quality and Location on Purchasing Decisions. The object of this research was consumers who visit the Wareg Cafe at JL Hibrida Raya 11 of Bengkulu City. The number of respondents was 112 people. The data collection method used was a questionnaire. The techniques used were multiple regression analysis techniques, the coefficient of determination test (R2), hypothesis testing T statistic test and F statistical test. The results of the research can be concluded that the Service Quality and location variables have a positive and significant effect on purchasing decisions.